2019
DOI: 10.1021/acs.jpcb.9b03803
|View full text |Cite
|
Sign up to set email alerts
|

Untangling Hydrogen Bond Networks with Ion Mobility Spectrometry and Quantum Chemical Calculations: A Case Study on H+XPGG

Abstract: Ion mobility spectrometry-mass spectrometry and quantum chemical calculations are used to determine the structures and stabilities of singly protonated XaaProGlyGly peptides: H + DPGG, H + NPGG, H + EPGG, and H + QPGG. The IMS distributions are similar, suggesting the peptides adopt closely related structures in the gas phase. Quantum chemical calculations show that all conformers seen in the experimental spectrum correspond to the cis configuration about the Xaa-Pro peptide bond, significantly different from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(22 citation statements)
references
References 97 publications
(141 reference statements)
0
22
0
Order By: Relevance
“…To begin analyzing the effect of hydrogen bonding on the entropic differences reported in the previous section, Table details the potential energy density, V ( r ), at the bond critical point (bcp) for each hydrogen bond of both tautomers shown in Figure , ordered from strongest to weakest. The previous study on D, N, E, and QPGG detailed the correlation between hydrogen-bond length and V ( r ), employing this quantity to detail changes in the hydrogen-bonding networks of cis species as the N-terminal residue was changed . Compared to the intricate and bifurcated hydrogen-bonding networks detailed in the previous studies, the hydrogen-bonding patterns seen in Figure are refreshingly simple.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…To begin analyzing the effect of hydrogen bonding on the entropic differences reported in the previous section, Table details the potential energy density, V ( r ), at the bond critical point (bcp) for each hydrogen bond of both tautomers shown in Figure , ordered from strongest to weakest. The previous study on D, N, E, and QPGG detailed the correlation between hydrogen-bond length and V ( r ), employing this quantity to detail changes in the hydrogen-bonding networks of cis species as the N-terminal residue was changed . Compared to the intricate and bifurcated hydrogen-bonding networks detailed in the previous studies, the hydrogen-bonding patterns seen in Figure are refreshingly simple.…”
Section: Resultsmentioning
confidence: 97%
“…The conformer making up the minor peak, Figure (A), will be referred to throughout this report as Nt- cis -1, with Nt referring to the placement of the excess proton on the N-terminal amino group, cis referring to the cis orientation of the Pro and Lys α carbons (illustrated by the green line in Figure (A)), and −1 referring to this being the lowest-lying Nt- cis conformer in terms of Gibbs free energy. Of relevance to the previous studies, Nt- cis -1 corresponds to the cis -1r structures reported in the study of H + XPGG, where X = D, N, E, and Q, with −1 r corresponding to a specific arrangement of the hydrogen-bonding network as well as an interaction between the C-terminal hydroxyl group and the N-terminal residue’s side chain . However, here we are more interested in the tautomers rather than individual conformers and number the structures of any given conformer of each tautomer by relative Gibbs free energies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations